Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cells11142132
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Cytokines and Chronic Lung Diseases

Abstract: IL-17 cytokines are expressed by numerous cells (e.g., gamma delta (γδ) T, innate lymphoid (ILC), Th17, epithelial cells). They contribute to the elimination of bacteria through the induction of cytokines and chemokines which mediate the recruitment of inflammatory cells to the site of infection. However, IL-17-driven inflammation also likely promotes the progression of chronic lung diseases, such as chronic obstructive pulmonary disease (COPD), lung cancer, cystic fibrosis, and asthma. In this review, we high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 149 publications
(206 reference statements)
0
25
0
Order By: Relevance
“…Multiple signaling pathways contribute to the development of pulmonary fibrosis as the IL-17 signaling pathway plays a direct or indirect role [22][23][24] . Interleukin 17 (IL-17) is a cytokine mainly derived from Th17 cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple signaling pathways contribute to the development of pulmonary fibrosis as the IL-17 signaling pathway plays a direct or indirect role [22][23][24] . Interleukin 17 (IL-17) is a cytokine mainly derived from Th17 cells.…”
mentioning
confidence: 99%
“…After IL-17 is attached to the receptor, it exerts biological activity by activating the mitogenic-activated protein kinase 18,19 . The stimulation of IL-17 signaling pathway promotes the inflammation and fibrosis in lung [20][21][22][23][24] . One study reported 25 that molecular, immunohistochemical, and flow cytometric analyses of human and mouse specimens determine the immune response before collagen deposition.…”
mentioning
confidence: 99%
“…In our study, plasma IL-17 was positively linear correlations with white cell count and neutrophil cell count. The reason may be related to the recruitment and activation of neutrophils by IL-17, which can effectively promote airway inflammation ( Ritzmann et al., 2022 ). The bronchiectasis severity index (BSI) was used to evaluate the severity of bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, 1,25-(OH)2D3 can effectively prevent Thl7 cells from secreting IL-17 (23). In stable COPD patients, IL-17 was expressed in the bronchial mucosa at a higher level than in the control group, and Th17 was crucial to the emergence and progression of chronic inflammation in COPD (24). 1,25-(OH)2D3 can greatly reduce Th17 generation, which is advantageous for disorders caused by T cell-mediated immunity (25).…”
Section: Vitamin D and Immune Regulationmentioning
confidence: 97%